Soviet Asia: economic development and National policy choices - "Dienes, Leslie" (Boulder, 1987)
This work examines the geographic position of soviet Asia in the overall economy of the USSR and analyzes the impact of major national policy issues on its development and prospects. The Asian USSR constitutes three-fourths of the country's territory, an area exceeding the size of Brazil and Australia combined. Its acquisition was the result of Russian expansion and conquest in the past 499 years. This vast territory is still hinterland to the European USSR, weakly and unevenly integrated into the country's economic and societal mainstream. Moreover, the Asian USSR is hardly unifonn, culturally or otherwise. Its regions play very different roles in the Soviet spatial system and are affected by different policy choices on the national level. On the one hand, there are striking contrasts between Moslem Central Asia and Siberia (including the Far East). On the other hand, the Siberian regions are also assigned different economic and strategic roles according to their resource environment, their links to the economic power centers in the European USSR (partly a function of their east-west and north-south positions) and their strategic vulnerability or importance.
Keywords: Siberia economic policy